2022
DOI: 10.3389/fnagi.2022.895430
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genetic Data in Selecting Device-Aided Therapies in Patients With Advanced Parkinson’s Disease: A Mini-Review

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disease. At present, 5–10% of PD patients are found to have monogenic form of the disease. Each genetic mutation has its own unique clinical features and disease trajectory. It is unclear if the genetic background can affect the outcome of device-aided therapies in these patients. In general, monogenic PD patients have satisfactory motor outcome after receiving invasive therapies. However, their long-term outcome can vary with their genetic mutations. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…However, a study [ 45 ] demonstrated that individuals with certain PRKN mutations have a better response to LD treatment, although they are possibly at a higher risk of developing dyskinesia compared to individuals without these PRKN mutations. In fact, recently, it has been suggested that mutations in PRKN could influence the onset of LID at an early stage, although this relationship has not yet been much explored [ 13 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study [ 45 ] demonstrated that individuals with certain PRKN mutations have a better response to LD treatment, although they are possibly at a higher risk of developing dyskinesia compared to individuals without these PRKN mutations. In fact, recently, it has been suggested that mutations in PRKN could influence the onset of LID at an early stage, although this relationship has not yet been much explored [ 13 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we highlight the PRKN gene (parkin RBR E3 ubiquitin protein ligase), also known as PARK2 or Parkin, being the gene most associated with autosomal recessive PD of early onset [ 11 , 12 , 13 ]. It encodes Parkin, a protein that regulates mitophagy and mitochondrial biogenesis, participating in the quality control system of mitochondria [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The converse is true for PARK-PRKN, where, on the whole, patients continue to show doparesponsiveness even in the long term, exhibit less cognitive decline, and respond relatively favorably to DBS [96,99,100]. These genetic factors are increasingly taken into consideration in the clinical management of patients, e.g., in the selection or counseling of patients for DBS [101,102], and bring the field one step closer to realizing a personalized precision medicine approach for people living with PD [1,3,[103][104][105]. In sporadic PD, besides their association with disease risk, PRSs have also shown predictive value in PD phenotype or clinical outcomes [14,106], such as age at disease onset [107]; motor progression [108]; development of dyskinesias [109], impulse control disorders [110] or cognitive decline (e.g., with one recent study reporting a hazard ratio of 4.8 for progression to PD dementia with the RIMS2 progression locus [111]); and response to medical (pharmacogenomics) [112] and surgical therapies ("surgicogenomics") [113,114].…”
Section: Besides Causation/development Of Disease Genetic Factors Can...mentioning
confidence: 99%
“…However, some knowledge that can be used exists, even at the present time, to make treatment decisions. For instance, better cognitive and worse motor scores with good levodopa (L-dopa) benefit predict a better long-term motor response to deep brain stimulation of the subthalamic nucleus, 24 some genetic variants predict a poorer response, 25 and dopamine agonists might be avoided in PRKN-associated PD due to increased risk of impulse control disorders (ICD). [26][27][28] More recently, genetic predictors of response to therapy in PD have been identified.…”
Section: Purpose #2: To Predict Response To Treatments In Clinical Pr...mentioning
confidence: 99%